PENGEMBANGAN MEDIA GOOGLE SITES BERBASIS KEARIFAN LOKAL PADA MATERI BAGIAN-BAGIAN TUMBUHAN DAN FUNGSINYA PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI 2 KUBUTAMBAHAN - Gede Cista Ferdiawan; I Made Ariasa Giri; Made Adi Nugraha Tristaningrat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The problem in learning science in elementary schools is the limited use of interactive and contextual digital learning media. In addition, the use of local wisdom in learning has not been done optimally so that learning is less meaningful for students. This study aims to describe the design, analyze the validity, and analyze the practicality of Google Sites media based on local wisdom on the material of plant parts and their functions for fourth-grade students of SD Negeri 2 Kubutambahan. This study uses the Research and Development (R&D) method with the development of the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 3 media experts, 3 material experts, 3 language experts, 2 fourth-grade teachers, and 35 fourth-grade students of SD Negeri 2 Kubutambahan. Data collection techniques were carried out through observation, interviews, documentation, and questionnaires. The resulting product is a Google Sites learning media based on local wisdom that integrates the values ​​of Tri Hita Karana and Tumpek Wariga into the material of plant parts and functions. This media is equipped with learning materials, images, videos, interactive practice exercises, evaluations, and learning activities accessible through digital devices. The results showed that the local wisdom-based Google Sites media received a validity score of 0.88 from media experts, 0.90 from material experts, and 0.94 from language experts, all of which fall into the very valid category. In the practicality test, teachers gave an 89% rating and students 98.2%, which falls into the very practical category. Based on these results, the local wisdom-based Google Sites media is declared very valid and very practical, making it suitable for use as a science learning medium for the topic of plant parts and their functions for fourth-grade elementary school students.